SERVICE QUALITY, BUSINESS ETHICS, AND GOVERNANCE OF BUYER-SUPPLIER RELATIONSHIP TO ENHANCE COMPETITIVENESS: CRITICAL LITERATURE REVIEW - Diem, Daisy Ade Riany; Marimin; Machfud; Anggraeni, Elisa (Jurnal Teknologi Industri Pertanian, 2024)
The aim of this study is to provide an objective overview in buyer-supplier relationship in manufacturing industries to enhance competitiveness in the context of service quality, business ethics, and relational governance. A systematic literature review was conducted using the PRISMA model and 53 papers were selected after had been screened. The results showed that: 1) research’s objects encompass various types of manufacturing industries, such as pulp & paper, chemical, mining, automotive, SMEs, and diverse organizations which came from 22 countries, whereas China, European countries, and African countries are likely paid intensive intension regarding the three dimensions of research’s objects. The methods used in existing studies mostly focused on factor analysis, qualitative/descriptive, and system dynamic. However, soft system was the least commonly utilized in buyer-supplier relationship in context of industries’ competitiveness, 2) Service quality positively affects customers’ satisfaction, trust, customer and brand loyalty, and it is also a strong mediator to green logistics performance. Customers’ perceptions on service quality and brand can take precedence over traditional competitive advantages due to increased level of competition and customers’ changing expectations. Adopting ethics as a policy could be an advantage for business to stay competitive. Furthermore, relational governance requires trust and information sharing so that building a trustworthy buyer-supplier relationship is critical for successful supply chain management, 3) Paper industry is still considered a research trend, therefore focusing in integrating both soft and hard systems approach for strategy development is the most appropriate in order to improve its’ competitiveness as the basis for upcoming research. Keywords: business ethics, competitiveness, relational governance, service quality, buyer-supplier relationship